Cancer survivors' adherence to the American cancer society and American institute of cancer research dietary guidelines in Lebanon - Jana Jabbour; Remie El Helou; Ruba Hadla; Riwa Azar; Maria Mezher; Farah Naja; Sally Temraz (BMC, 2024)
Abstract Background Adequate diet and lifestyle practices are postulated to improve health and enhance wellbeing of cancer survivors. Despite the heavy cancer burden in Lebanon, little is known about the diet quality of survivors. This cross-sectional study assessed the compliance of survivors in remission with the American Cancer Society/American Institute Research Fund (ACS/AICR) diet and physical activity guidelines. Methods Cancer survivors in remission for at least 3 months and attending oncology clinics in two referral centers in Beirut, Lebanon were recruited. Adherence to the ACS/AICR was assessed by examining the compliance to guidelines promoting fruits, vegetables and whole grain and discouraging elevated alcohol, meat and energy dense foods intake. Dietary data was assessed through food frequency and lifestyle questionnaires administered face to face and through phone interviews. Anthropometrics, food security and sociodemographic data was also collected. Univariate and bivariate descriptive and logistic regressions were used to determine predictors of adherence rates to the ACS/AICR score. Results A total of 268 participants were recruited (mean age = 59 ± 23 years, 83% females, 70% breast cancer). Mean time since remission was 3.2 ± 4 years and the majority (72%) had food insecurity. Low physical activity and overweight/obesity were present in 65% and 67% of the survivors, respectively. Median adherence score with the ACS/AICR score was 9.0 out of 15. The majority of survivors had complete adherence to the moderate meat and alcohol consumption guidelines. However, 98% were noncompliant with the whole grains' consumption guidelines. Cancer type, site of recruitment and education were the significant predictors of the ACS/AICR diet adherence score. Conclusion This study highlights the elevated rates of overweight/obesity, physical inactivity and the alarmingly low adherence with the whole grains consumption guideline among cancer survivors in remission. Policy makers ought to use study findings to redirect government subsidization and educational interventions in the country and physicians should stress the importance of adherence to a healthy diet during remission through counseling and timely referral.